Method for improving wear resistance of riveting head of automobile hinge spin riveting machine

By using a high-energy density laser beam to prepare diamond particles-enhanced composite coating on the mandrel insert working surface of the rivet head of the automotive hinge rivet machine, the serious wear problem of rivet head in high-intensity and high-frequency operating environments is solved, and the wear resistance and service life are significantly improved.

CN119913505AActive Publication Date: 2025-05-02CHANGCHUN SANYOU AUTOMOTIVE PARTS MFG CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510414484.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2025-05-02
Estimated Expiration
2045-04-03

AI Technical Summary

Technical Problem

The rivet head of the automotive hinge rotary riveter is prone to wear in high-strength and high-frequency operating environments, resulting in a shortened service life, increasing production costs and downtime, and affecting the consistency and reliability of the product.

Method used

A high-hardness, high wear-resistant composite coating based on diamond particles reinforced by diamond particles is prepared using a high-energy-density laser beam to form a wear-resistant coating with metallurgical bonding.

Benefits of technology

It significantly improves the wear resistance and service life of the rivet head, reduces the replacement and trimming frequency of the rivet head, extends the working time of the rivet machine, and maintains excellent performance in a harsh working environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913505A_ABST
    Figure CN119913505A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of laser beam processing, and relates to a method for improving the wear resistance of a riveting head of an automobile hinge spin riveting machine, which comprises the following steps: preparing composite coating alloy powder, adding diamond particles as a main reinforcing component to obviously improve the wear resistance of a coating, and carrying out ball milling and powder mixing to obtain the composite coating alloy powder; the surface of the rivet head mandrel insert is pretreated; carrying out laser melting deposition to prepare a diamond particle reinforced wear-resistant layer; and after-treatment of the wear-resistant coating, polishing the surface of the coating. According to the method, the coating alloy is heated and melted on the working face of the spindle insert of the riveting head of the spin riveting machine through the high-energy-density laser beam, the coating alloy is rapidly solidified and forms metallurgical bonding with the base body, the high-hardness wear-resistant coating is formed on the working face of the spindle insert, and the coating has higher hardness and wear resistance and can effectively resist friction and impact; the excellent performance is kept in a harsh working environment, the working time of the riveting head of the rotary riveting machine is greatly prolonged, the service life of the riveting head is prolonged, and the replacement and trimming frequency of the riveting head is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser beam processing, and in particular relates to a method for improving the wear resistance of a rivet head of an automobile hinge riveting machine. Background Art

[0002] As the core component that connects car doors, hoods and other parts to the car body, the connection strength and service life of the car hinge will directly affect the safety and reliability of the vehicle. At present, the car hinge generally adopts the rotary riveting process to achieve the precise connection between rivets and metal sheets. The rotary riveting process is to place the rivet at a predetermined riveting position, and the rivet head starts to rotate at high speed and apply pressure, so that the rivet is gradually pressed into the connector, and then through the action of rotation and pressure, the rivet head undergoes plastic deformation to form a strong connection. Compared with welding or bolting, the rotary riveting process can avoid the risk of thermal deformation and reduce assembly stress. At the same time, it meets the requirements of lightweight automobiles for high-precision connections. However, the rotary riveting process of automobile hinges is characterized by high frequency and high load.

[0003] Taking the door hinge as an example, a single production line needs to complete tens of thousands of riveting operations every day, and the rivet head needs to withstand instantaneous impact loads of up to 500-800MPa. Therefore, the rivet head faces serious wear problems in actual application, especially in high-intensity and high-frequency operating environments. First, the rivet head is subjected to high pressure and friction for a long time during high-frequency use, which causes rapid wear on its surface. The wear not only affects the riveting quality, but also shortens the service life of the rivet head. Secondly, due to severe wear, the service life of the rivet head is short and needs to be replaced frequently, which not only increases production costs, but also increases the downtime of the production line, affecting production efficiency. The worn rivet head may lead to a decline in riveting quality and unsatisfactory fixing effect of the rivet, affecting the consistency and reliability of the product.

[0004] Usually, rivet heads are made of materials such as carbon tool steel, high-speed steel, cemented carbide and tungsten alloy. Among them, carbon tool steel has poor wear resistance and impact resistance, and is easy to wear or break under high-intensity use conditions. High-speed steel includes M2, M35, etc., which are expensive and prone to brittle fracture under extreme working conditions. Commonly used cemented carbide grades are YG6, YG8, etc. Traditional rivet head materials, such as ordinary steel or cemented carbide, do not perform well in high-intensity working environments and are difficult to meet the requirements of modern manufacturing for high wear resistance. Tungsten alloy is an alloy material made of tungsten as a matrix and with appropriate amounts of cobalt, nickel and other elements. It has the characteristics of extremely high hardness, excellent wear resistance, good toughness, and can maintain good stability under high stress conditions. Commonly used tungsten alloys include W90Cu10, etc. However, tungsten alloys are expensive and difficult to process.

[0005] To this end, the prior art has proposed a variety of methods to improve the wear resistance and service life of the rivet head. For example, high-chromium cast iron, ceramic materials and superhard materials among high-hardness materials are used as the substrate of the rivet head. Although the above materials have high hardness and wear resistance, they face the risk of high brittleness in practical applications, are prone to fracture under high stress conditions, and are expensive and difficult to process, which is not conducive to large-scale application. In addition, it is proposed to form a layer of hard coating (such as TiN, CrN) on the surface of the rivet head through surface heat treatment or surface coating technology (such as physical vapor deposition PVD, chemical vapor deposition CVD) to improve the hardness and wear resistance of the surface. However, this method has the problem that a single coating is easy to fall off or wear during high-intensity use, affecting the wear resistance effect, and it is difficult to meet the requirements of high hardness and high toughness at the same time. Studies have shown that the hardness and toughness of the rivet head substrate can be enhanced by heat treatment processes such as quenching and tempering. However, the traditional heat treatment process has the problem of difficulty in accurately controlling temperature and time, which easily leads to unstable performance of the rivet head, and the material is easily deformed during the heat treatment process, which affects the accuracy and service life of the rivet head.

[0006] In summary, although the existing technology has improved the performance of the rivet head to a certain extent, it still has many shortcomings such as poor coating adhesion, complex process, high cost, high material brittleness and difficult processing. At present, automobile manufacturing is upgrading towards intelligence and high-beat. Traditional material improvement methods still have significant bottlenecks in terms of cost, process compatibility and wear resistance balance, and it is difficult to meet the needs of actual industrial production. Based on this, it is very necessary to develop a more efficient and cost-controlled method to improve the wear resistance of the rivet head, which is of great significance to improving the manufacturing quality of automobile hinges and the overall efficiency of the production line. Summary of the invention

[0007] The purpose of the present invention is to provide a method for improving the wear resistance of the rivet head of a car hinge rotary riveting machine. A high-hardness, high-wear-resistant composite coating based on diamond particle reinforcement is prepared by applying a high-energy-density laser beam to the working surface of the mandrel insert of the rivet head of the rotary riveting machine, and a wear-resistant coating is formed on the working surface of the mandrel insert to solve the problem of significantly improving the wear resistance of the rivet head and extending its service life.

[0008] The objective of the present invention is achieved through the following technical solutions: A method for improving the wear resistance of a rivet head of a car hinge riveting machine, using a laser beam to prepare a composite coating based on diamond particles and having metallurgical bonding on the working surface of a mandrel insert 2 of the rivet head of the riveting machine, comprising the following steps: A. Preparation of composite coating alloy powder: The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is calculated by mass percentage Wt / %: nickel is 24-26, cobalt is 32-36, diamond is 0.5-1, and tungsten is the balance; firstly, nickel powder, cobalt powder, diamond particles and tungsten powder are weighed and mixed evenly, and then ball milled for 12 hours to obtain the composite coating alloy powder; wherein the particle size of the diamond particles is not greater than 100nm; B. Treatment of the surface of the mandrel insert 2 of the rivet head: Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface; C. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles; The composite coating alloy powder obtained in step A is added into the powder feeding bin, and the composite coating alloy powder is melted by a high energy density laser beam to obtain a wear-resistant coating 3 with a thickness of 400-800 μm on the end face of the high-speed steel; wherein the laser melting deposition process parameters are: laser power 1.5-3 kW, scanning speed 180-240 mm / min, powder feeding speed 30-35 g / min, protective gas flow rate 15-18 L / min, and a wear-resistant coating 3 with metallurgical bonding is formed on the working surface of the mandrel insert 2 of the rivet head; D. Post-treatment of the wear-resistant coating 3: Use a 5000-mesh polishing wheel at a speed of 1500 rpm to polish the surface of the wear-resistant coating 3 for 5 minutes to remove possible flaws or uneven areas on the surface, improve the smoothness and performance of the coating, and meet the design requirements.

[0009] Furthermore, in step A, the purity of the tungsten, nickel and cobalt used is greater than 99.9%, and the particle size of the powder is 75-80 μm.

[0010] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 26, cobalt is 32, diamond is 0.5, and tungsten is the balance.

[0011] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 26, cobalt is 33, diamond is 0.8, and tungsten is the balance.

[0012] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 25, cobalt is 34, diamond is 1, and tungsten is the balance.

[0013] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 25, cobalt is 35, diamond is 0.5, and tungsten is the balance.

[0014] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 24, cobalt is 36, diamond is 0.8, and tungsten is the balance.

[0015] Furthermore, in step A, the alloy composition of the composite coating is calculated by mass percentage Wt / % as follows: nickel is 24, cobalt is 36, diamond is 1, and tungsten is the balance.

[0016] Furthermore, in step A, the ball milling process is specifically as follows: three types of zirconia ball milling beads with diameters of 12 mm, 6 mm and 1 mm are selected, with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1, the powder and the balls are placed in a ball milling jar, and argon gas is filled in for protection for ball milling. The ball milling speed is 250 r / min, each ball milling is 10 minutes, and then stopped for 10 minutes for heat dissipation, and the ball milling is performed for 12 hours.

[0017] Further, in step C, the energy density of the laser beam is in the range of 1-10 kW / cm².

[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention applies a high-energy-density laser beam to heat and melt the coating alloy on the working surface of the mandrel insert of the automobile hinge rotary riveting machine, and rapidly solidifies it to form a metallurgical bond with the substrate, thereby forming a high-hardness and wear-resistant coating on the working surface of the mandrel insert. The coating hardness in the prior art is 58-62 HR. Compared with traditional materials, the coating of the present invention has higher hardness and wear resistance, can effectively resist friction and impact, and maintain excellent performance in harsh working environments. In the prior art, the rivet head is generally severely worn after about 15,000 rivetings. The present invention greatly improves the working time of the rivet head of the rotary riveting machine, extends the service life of the rivet head, and reduces the frequency of replacement and repair of the rivet head. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 This is a schematic diagram of the process of the rotary riveting principle; Figure 2 Schematic diagram of the structure of the wear-resistant coating prepared by laser melting deposition in the present invention; Figure 3 This is a scan of the wear surface of the rivet head of a rotary riveting machine after 15,000 rivetings without wear-resistant coating; Figure 4 This is a scan of the wear surface of the rivet head of a rotary riveting machine after 15,000 riveting cycles after the wear-resistant coating was prepared by laser melting deposition.

[0021] In the figure, 1. mandrel; 2. mandrel insert; 3. wear-resistant coating; 4. rivet; 5. workpiece. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with embodiments: The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention. It should also be noted that, for ease of description, only parts related to the present invention, rather than all structures, are shown in the accompanying drawings.

[0023] It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. At the same time, in the description of the present invention, the terms "first", "second", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance.

[0024] Figure 1 This is the basic principle of the spin riveting process. During the spin riveting process, the mandrel 1 applies axial pressure while rotating, and the tail of the rivet 4 is plastically deformed through the mandrel insert 2 to fit the workpiece 5 tightly, thereby achieving a stable connection of the workpiece 5.

[0025] like Figure 1-Figure 2 As shown, the mandrel 1 is the main body of the entire rivet head of the rotary riveting machine, transmitting rotational motion and pressure. The mandrel insert 2 is located at the bottom of the mandrel 1 and is in direct contact with the rivet 4 to guide the plastic deformation of the tail of the rivet 4. A layer of wear-resistant coating 3 is prepared on the surface of the mandrel insert 2 by laser melting deposition. The thickness of the wear-resistant coating 3 is 400-800μm, which is used to enhance wear resistance, greatly improve the working time of the rivet head of the rotary riveting machine, extend the service life of the rivet head, and reduce the replacement and trimming frequency of the rivet head.

[0026] The present invention provides a method for improving the wear resistance of a rivet head of a rotary riveting machine. A high-energy-density laser beam is applied to the working surface of a mandrel insert 2 of the rivet head of the rotary riveting machine to melt a specific composite coating material, so as to prepare a high-hardness and high-wear-resistant composite alloy material reinforced with diamond particles, and a wear-resistant coating 3 with metallurgical bonding is formed on the working surface of the mandrel insert 2, thereby significantly improving the wear resistance of the rivet head and extending its service life.

[0027] The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine of the present invention comprises the following steps: The first step is to prepare a composite coating alloy powder. The composite coating alloy powder of the present invention is composed of nickel powder, cobalt powder, diamond particles and tungsten powder to enhance the overall strength and wear resistance of the coating, and its composition is calculated by weight percentage (Wt / %): nickel (Ni): 24-26, cobalt (Co): 32-36, diamond 0.5-1, tungsten (W): balance.

[0028] The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, and the particle size of the powder is 75-80 μm. The present invention adds a certain amount of diamond particles, which are used as the main reinforcing component. Diamond has extremely high hardness and wear resistance, and can significantly improve the wear resistance of the coating. The rigidity and wear resistance during the riveting process are guaranteed, thereby avoiding rapid wear and failure of the end face of the rivet head. The particle size of the diamond particles is not greater than 100 nm.

[0029] The present invention adopts ball milling to mix powder to obtain basic alloy powder with uniform composition. Specifically, the four powders are accurately weighed according to mass percentage by an electronic balance with an accuracy of 0.0001g, three zirconium oxide ball milling beads with diameters of 12mm, 6mm and 1mm are selected, the weight ratio is 1:1:1, and the ball-to-material ratio is 4:1, the powder and the ball are put into a ball milling jar, and argon gas is filled in for protection to perform ball milling, the ball milling speed is 250 r / min, each ball milling is performed for 10min, and then stopped for 10min to dissipate heat, and the composite coating alloy powder is obtained by ball milling for 12h.

[0030] The second step is pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0031] The third step is laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. Specifically, a high-energy-density laser beam device is used, and the energy density of the laser beam is usually in the range of 1-10 kW / cm², which can effectively melt and deposit the composite coating material. The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 400-800μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 1.5-3kw, scanning speed 180-240mm / min, powder feeding speed 30-35g / min, shielding gas flow 15-18L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0032] The fourth step is post-processing of the wear-resistant coating 3. A 5000-mesh polishing wheel is used to polish the surface of the wear-resistant coating 3 at a speed of 1500 rpm for 5 minutes to remove possible defects or uneven areas on the surface, improve the smoothness and performance of the coating, and meet the design requirements.

[0033] Embodiment 1: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is by mass percentage (Wt / %): nickel (Ni): 26, cobalt (Co): 32, diamond 0.5, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0034] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0035] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0036] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. A high-energy-density laser beam device is used, and the energy density of the laser beam is 1kW / cm². The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 400μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 1.5kw, scanning speed 180mm / min, powder feeding speed 30g / min, protective gas flow 15L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0037] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0038] Embodiment 2: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is by mass percentage (Wt / %): nickel (Ni): 26, cobalt (Co): 33, diamond 0.8, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0039] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0040] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0041] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. A high-energy-density laser beam device is used, and the energy density of the laser beam is 2 kW / cm². The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 500μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 1.8 kw, scanning speed 200mm / min, powder feeding speed 31g / min, shielding gas flow rate 15L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0042] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0043] Embodiment 3: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is calculated by mass percentage (Wt / %): nickel (Ni): 25, cobalt (Co): 34, diamond 1, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0044] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0045] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0046] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. A high-energy-density laser beam device is used, and the energy density of the laser beam is 5 kW / cm². The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 600μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 2kw, scanning speed 200mm / min, powder feeding speed 32g / min, shielding gas flow 16L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0047] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0048] Embodiment 4: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is by mass percentage (Wt / %): nickel (Ni): 25, cobalt (Co): 35, diamond 0.5, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0049] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0050] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0051] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. Use high-energy-density laser beam equipment, and the energy density of the laser beam is in the range of 6kW / cm². Add the composite coating alloy powder into the powder feeding bin, melt the composite coating alloy powder by laser beam, and obtain a wear-resistant coating 3 with a thickness of 600μm on the end face of high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 2.4kw, scanning speed 220mm / min, powder feeding speed 33g / min, shielding gas flow 17L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0052] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0053] Embodiment 5: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is by mass percentage (Wt / %): nickel (Ni): 24, cobalt (Co): 36, diamond 0.8, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0054] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0055] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0056] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. A high-energy-density laser beam device is used, and the energy density of the laser beam is 8 kW / cm². The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 700μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 2.8kw, scanning speed 220mm / min, powder feeding speed 34g / min, shielding gas flow 17L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0057] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0058] Embodiment 6: A method for improving the wear resistance of a rivet head of a car hinge riveting machine comprises the following steps: 1. Prepare composite coating alloy powder. The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is calculated by mass percentage (Wt / %): nickel (Ni): 24, cobalt (Co): 36, diamond 1, tungsten (W): balance. The purity of the metal tungsten, nickel and cobalt used is greater than 99.9%, the particle size of the powder is 75-80μm, and the particle size of the diamond particles is not greater than 100nm.

[0059] The above four powders were accurately weighed according to the mass percentage using an electronic balance with an accuracy of 0.0001g. Three zirconia ball milling beads with diameters of 12mm, 6mm and 1mm were selected with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1. The powders and balls were placed in a ball milling jar, which was filled with argon gas for protection and ball milling was carried out at a speed of 250 r / min. The ball milling was performed for 10min each time, and then stopped for 10min to dissipate heat. The composite coating alloy powder was obtained after ball milling for 12h.

[0060] 2. Pretreatment. Clean and surface treat the mandrel insert 2 of the rivet head to remove the oxide layer and impurities, and use an acetone solution with a purity of more than 99% to ultrasonically clean the insert end face at an ultrasonic frequency of 50kHz for 10 minutes to ensure a clean surface.

[0061] 3. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles. A high-energy-density laser beam device is used, and the energy density of the laser beam is 10 kW / cm². The composite coating alloy powder is added to the powder feeding bin, and the composite coating alloy powder is melted by the laser beam to obtain a wear-resistant coating 3 with a thickness of 800μm on the end face of the high-speed steel. The laser melting deposition process parameters obtained by optimization are: laser power 3kw, scanning speed 240mm / min, powder feeding speed 35g / min, shielding gas flow 18L / min, and a metallurgically bonded wear-resistant coating 3 is formed on the working surface of the mandrel insert 2 of the rivet head.

[0062] 4. Post-treatment of the wear-resistant coating 3: polish the surface of the wear-resistant coating 3 for 5 minutes at a speed of 1500 rpm using a 5000-mesh polishing wheel to remove possible flaws or uneven areas on the surface and improve the smoothness and performance of the coating.

[0063] The technical indicators achieved by the composite coating alloy wear-resistant layer of the rotary riveting machine rivet head prepared using the coating alloy composition, process steps and parameters of Examples 1 to 6 are shown in Table 1.

[0064] Table 1

[0065] It can be seen from Table 1 that the hardness of the wear-resistant layer of the composite coating alloy of the present invention is 75-85 HRC; the wear resistance of the composite coating alloy is 1.6-1.8 times that of the substrate without coating.

[0066] Depend on Figure 3 and Figure 4 It can be seen that the rivet head of the rotary riveting machine without the wear-resistant coating 3 is seriously worn after 15,000 rivetings and can no longer be riveted. The rivet head of the rotary riveting machine prepared according to the above process steps and components of the present invention has a smooth surface of the mandrel insert 2 after 15,000 continuous rivetings and can continue to be riveted. In the final test, it is not seriously worn until 27,000 to 30,000 continuous rivetings. The number of rivetings is 1.8 to 2 times that of the rivet head of the rotary riveting machine without the wear-resistant coating 3.

[0067] Note that the above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention has been described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.

Claims

1. A method for improving the wear resistance of the rivet head of an automobile hinge riveting machine, characterized in that: A composite coating having metallurgical bonding and reinforced with diamond particles is prepared on the working surface of a mandrel insert (2) of a rivet head of a rotary riveting machine by using a laser beam, comprising the following steps: A. Preparation of composite coating alloy powder: The composite coating alloy powder is composed of nickel powder, cobalt powder, diamond particles and tungsten powder, and its composition is calculated by mass percentage Wt / %: nickel is 24-26, cobalt is 32-36, diamond is 0.5-1, and tungsten is the balance; firstly, nickel powder, cobalt powder, diamond particles and tungsten powder are weighed and mixed evenly, and then ball milled for 12 hours to obtain the composite coating alloy powder; wherein the particle size of the diamond particles is not greater than 100nm; B. Surface treatment of the mandrel insert (2) of the rivet head: The mandrel insert (2) of the rivet head is cleaned and surface treated to remove the oxide layer and impurities, and the insert end face is ultrasonically cleaned using an acetone solution with a purity of more than 99% at an ultrasonic frequency of 50 kHz for 10 minutes to ensure that the surface is clean; C. Laser melting deposition to prepare a wear-resistant layer reinforced with diamond particles; The composite coating alloy powder obtained in step A is added to a powder feeding bin, and a high-energy density laser beam is used to melt the composite coating alloy powder to obtain a wear-resistant coating (3) with a thickness of 400-800 μm on the end face of the high-speed steel; wherein the laser melting deposition process parameters are: laser power 1.5-3 kW, scanning speed 180-240 mm / min, powder feeding speed 30-35 g / min, and shielding gas flow rate 15-18 L / min, and a wear-resistant coating (3) with metallurgical bonding is formed on the working surface of the mandrel insert (2) of the rivet head; D. Post-treatment of the wear-resistant coating (3): polish the surface of the wear-resistant coating (3) for 5 minutes using a 5000-grit polishing wheel at a speed of 1500 rpm to remove possible flaws or uneven areas on the surface, improve the smoothness and performance of the coating, and meet the design requirements.

2. The method for improving the wear resistance of the rivet head of the automobile hinge riveting machine according to claim 1, characterized in that: In step A, the purity of the tungsten, nickel and cobalt used is greater than 99.9%, and the particle size of the powder is 75-80 μm.

3. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 26, cobalt is 32, diamond is 0.5, and tungsten is the balance.

4. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 26, cobalt is 33, diamond is 0.8, and tungsten is the balance.

5. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 25, cobalt is 34, diamond is 1, and tungsten is the balance.

6. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 25, cobalt is 35, diamond is 0.5, and tungsten is the balance.

7. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 24, cobalt is 36, diamond is 0.8, and tungsten is the balance.

8. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A: The alloy composition of the composite coating is calculated by weight percentage Wt / % as follows: nickel is 24, cobalt is 36, diamond is 1, and tungsten is the balance.

9. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: Step A, the ball milling process is specifically as follows: select three types of zirconia ball milling beads with diameters of 12 mm, 6 mm and 1 mm, with a weight ratio of 1:1:1 and a ball-to-material ratio of 4:1, put the powder and the ball into a ball milling jar, fill it with argon gas for protection and perform ball milling, the ball milling speed is 250 r / min, each ball milling lasts 10 minutes, stops for 10 minutes for heat dissipation, and the ball milling lasts 12 hours.

10. The method for improving the wear resistance of the rivet head of an automobile hinge riveting machine according to claim 1, characterized in that: In step C, the energy density of the laser beam is in the range of 1-10 kW / cm².

Citation Information

Patent Citations

  • Laser preparation method of erosion-resistant surface layer of spherical body of ball valve in coal chemical industry

    CN104593766A

  • Method for preparing antifriction wear-resistant coating on metal matrix surface

    CN104962909A

  • Foam skeleton structure reinforced metal-matrix composite material and preparation method

    CN105779804A

  • Method for improving heavy-load wheel rail wear-resistant performance by laser cladding cobalt alloy coating

    CN107099793A

  • High-corrosion-resistance nickel-tungsten-based alloy multilayer cladding layer and preparing technology thereof

    CN110699724A